1996
DOI: 10.1002/(sici)1098-2345(1996)39:1<17::aid-ajp2>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Reproduction in captive lion tamarins (Leontopithecus): Seasonality, infant survival, and sex ratios

Abstract: Diversity in reproductive and social systems characterizes the primate family Callitrichidae. This paper contributes to our appreciation of this diversity by presenting the first detailed comparative analysis of captive breeding in three species of lion tamarins (Leontopithecus chrysomelas, L. chrysopygus, and L. rosalia) housed at the Centro de Primatologia do Rio de Janeiro. The annual pattern of reproduction in all three species of Leontopithecus was markedly seasonal, with births occurring during the sprin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…Moreover, there is a clear birth peak in September and October in Brazil, for both captiveand wild-born females. French et al [1996] also reported a clear birth peak in September and October for golden, golden-headed, and black lion tamarins housed at Centro de Primatologia do Rio de Janeiro (also included in this study); however, they did not differentiate between captive-and wild-born females. Kleiman et al [1982] noted seasonal breeding in captive L. rosalia, housed in the Northern hemisphere, with births being concentrated in March-September.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Moreover, there is a clear birth peak in September and October in Brazil, for both captiveand wild-born females. French et al [1996] also reported a clear birth peak in September and October for golden, golden-headed, and black lion tamarins housed at Centro de Primatologia do Rio de Janeiro (also included in this study); however, they did not differentiate between captive-and wild-born females. Kleiman et al [1982] noted seasonal breeding in captive L. rosalia, housed in the Northern hemisphere, with births being concentrated in March-September.…”
Section: Discussionmentioning
confidence: 90%
“…All group members provide infant care. Seasonality of breeding has been described for both wild [e.g., Goldizen et al, 1988;Stevenson & Rylands, 1988;Soini, 1988;Dietz et al, 1994] and captive [e.g., Brand, 1980;French et al, 1996;Sousa et al, 1999] populations of callitrichids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical studies support the view that the birth sex ratio at a population level is usually close to 1:1 (Ml ıkovsk y 1988;Bent & Reason 1998;Faust & Thompson 2000;Visscher et al 2004;Roche et al 2006;Nov akov a et al 2010). Nevertheless, numerous other studies report significant deviations from an equal sex ratio for individual parents (Clutton-Brock & Iason 1986;French et al 1996;Landete-Castillejos et al 2001;Cameron & Linklater 2007;Du sek et al 2011). However, many studies reporting variance in birth sex ratio suffered from the use of positive selective evidence (Clutton-Brock & Iason 1986;Festa-Bianchet 1996;Cockburn et al 2002;Krackow 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The captive population of the golden lion tamarin ( Leontopithecus rosalia ) was on the brink of extinction in the 1970s, but, following a new husbandry protocol, it began to breed well in captivity, establishing a self-sustaining population and supplying individuals for a successful re-stocking program in the Poço dos Antas Reserve (Kleiman et al 1991). Two other species, Leontopithecus chrysomelas and L. chrysopygus , are now breeding well in a number of zoos throughout the world (French et al 1996). In fact, one of the major problems of many current zoo captive breeding programs is the control of population growth (e.g., van Elsacker et al 1994).…”
mentioning
confidence: 99%